Enhanced therapeutic effect of APAVAC immunotherapy in combination with dose-intense chemotherapy in dogs with advanced indolent B-cell lymphoma. Issue 39 (22nd September 2015) - Marconato, L.; Stefanello, D.; Sabattini, S.; Comazzi, S.; Riondato, F.; Laganga, P.; Frayssinet, P.; Pizzoni, S.; Rouquet, N.; Aresu, L.
Highlights Canine indolent B-cell lymphoma of advanced clinical stage is an incurable disease. Autologous heat shock proteins induced immunity against DLBCL in a canine trial. Chemo-immunotherapy improved time to progression in dogs with indolent lymphoma. Dogs mounting an immune response lived significantly longer. There were no vaccine-related side effects.